2007
DOI: 10.1242/dev.02859
|View full text |Cite
|
Sign up to set email alerts
|

ADrosophilaortholog of the human cylindromatosis tumor suppressor gene regulates triglyceride content and antibacterial defense

Abstract: The cylindromatosis (CYLD) gene is mutated in human tumors of skin appendages. It encodes a deubiquitylating enzyme (CYLD) that is a negative regulator of the NF-B and JNK signaling pathways, in vitro. However, the tissue-specific function and regulation of CYLD in vivo are poorly understood. We established a genetically tractable animal model to initiate a systematic investigation of these issues by characterizing an ortholog of CYLD in Drosophila. Drosophila CYLD is broadly expressed during development and, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
55
1
4

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 49 publications
2
55
1
4
Order By: Relevance
“…CYLD is a deubiquitinating enzyme that downregulates mammalian TNFR signaling by inactivating TRAF2. Drosophila CYLD interacts with the IKK protein Kenny and also negatively regulates Imd signaling (75,76). Activated Relish is targeted for ubiquitination and proteasomal degradation by the SCF complex (77), possibly promoted by the ubiquitin-binding protein dRYBP (78).…”
Section: Regulation Of the Imd Signaling Pathwaymentioning
confidence: 99%
“…CYLD is a deubiquitinating enzyme that downregulates mammalian TNFR signaling by inactivating TRAF2. Drosophila CYLD interacts with the IKK protein Kenny and also negatively regulates Imd signaling (75,76). Activated Relish is targeted for ubiquitination and proteasomal degradation by the SCF complex (77), possibly promoted by the ubiquitin-binding protein dRYBP (78).…”
Section: Regulation Of the Imd Signaling Pathwaymentioning
confidence: 99%
“…8 Two recent studies have shown that CYLD also regulates NF-κB and JNK signaling in Drosophila. 10,12 Xue et al 12 demonstrated that CYLD deficiency suppressed activated JNK signaling and abolished JNK dependent transcription during wing development, consistent with a positive role for CYLD. Furthermore, dTRAF2 exhibited enhanced ubiquitination concomitantly with reduced protein levels in this mutant, suggesting CYLD removes a degradative ubiquitin modification that stabilises dTRAF2 to promote JNK signaling (Fig.…”
mentioning
confidence: 88%
“…The NF-κB inhibitory function of CYLD has been confirmed in mouse and Drosophila organisms, where mutations that strongly reduced CYLD mRNA/protein levels caused enhanced susceptibility to NF-κB stimuli. [7][8][9][10] CYLD was also shown to negatively regulate JNK activation in cultured mammalian cells and positively regulate the signaling pathway in developing Drosophila 11,12 (Fig. 1).…”
mentioning
confidence: 97%
See 2 more Smart Citations